1986
DOI: 10.1093/infdis/154.1.76
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B-Induced Oxidative Damage and Killing of Candida albicans

Abstract: Amphotericin B (AmB) is known to bind to ergosterol in fungal cell membranes, but the precise mechanism of its toxicity to cells is as yet poorly understood. AmB autooxidizes, and it is possible that its antifungal effects could result from oxidative damage. Exposure of protoplasts of Candida albicans to AmB under hypoxic conditions reduced protoplast lysis by as much as 80% compared with incubations in air. Protoplasts were protected from AmB-induced lysis by exogenous catalase and/or superoxide dismutase (SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
148
1
6

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(167 citation statements)
references
References 20 publications
9
148
1
6
Order By: Relevance
“…Our results revealed that SOD activity was signifi cantly increased in C. dubliniensis and C. albicans strains that were resistant to amphotericin B and fl uconazole compared to sensitive strains. The increase in SOD activity in response to amphotericin B may be due to the production of oxidative damage in Candida through lipid peroxidation 15 . In our study, yeast cultures were exposed to increasing concentrations of amphotericin B, up to a maximum of 2 µg ml -1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results revealed that SOD activity was signifi cantly increased in C. dubliniensis and C. albicans strains that were resistant to amphotericin B and fl uconazole compared to sensitive strains. The increase in SOD activity in response to amphotericin B may be due to the production of oxidative damage in Candida through lipid peroxidation 15 . In our study, yeast cultures were exposed to increasing concentrations of amphotericin B, up to a maximum of 2 µg ml -1 .…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme catalase converts hydrogen peroxide (H 2 O 2 ) to oxygen (O 2 ) and water (H 2 O) 16 . In Candida, catalase has been suggested to be involved in the resistance to amphotericin B and is involved in hypha formation 15,28 . Catalase activity has not been previously studied in fl uconazole-resistant C. albicans and C. dubliniensis strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because AmB stimulates Fc-mediated ingestion and because it is known to exert some of its biological and toxic effects by the generation of reactive oxygen metabolites (9), we have investigated activation of the respiratory burst as a possible mechanism for regulation of phagocytic function. Superoxide and hydrogen peroxide production are known to accompany phagocytosis (10).…”
Section: Introductionmentioning
confidence: 99%
“…27 A second effect of amphotericin B is thought to be cell damage secondary to drug autooxidation. 33 …”
Section: Mode Of Actionmentioning
confidence: 99%